2021
DOI: 10.1111/nep.13961
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the first and secondCOVID‐19 wave on kidney transplant recipients at a large Indian transplant centre

Abstract: Background There is a scarcity of data comparing the consequences of first and second COVID‐19 waves on kidney transplant recipients (KTRs) in India. Methods We conducted a single‐centre retrospective study of 259 KTRs with COVID‐19 to compare first wave (March 15–December 31 2020, n = 157) and second wave (April 1–May 31 2021, n = 102). Results KTRs during second wave were younger (43 vs. 40 years; p ‐value .04) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…A study in Gujarat reported similar mortality due to Covid-19 among renal transplant recipients in the second vs first wave. 25 In this study of 259 renal-transplant recipients (first wave 157, second wave 102) there was no difference in presenting clinical and biochemical presentation while incidence of invasive mucormycosis and ICU admission was greater in second wave with insignificant differences in mortality in the two waves (9.6% vs 10.0%). In the present study we observed greater mortality in both second and first waves as compared to these Indian studies (19.3% vs 11.5%).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A study in Gujarat reported similar mortality due to Covid-19 among renal transplant recipients in the second vs first wave. 25 In this study of 259 renal-transplant recipients (first wave 157, second wave 102) there was no difference in presenting clinical and biochemical presentation while incidence of invasive mucormycosis and ICU admission was greater in second wave with insignificant differences in mortality in the two waves (9.6% vs 10.0%). In the present study we observed greater mortality in both second and first waves as compared to these Indian studies (19.3% vs 11.5%).…”
Section: Discussionmentioning
confidence: 56%
“…21,22 There are only limited studies that have compared the clinical features and outcomes in Covid-19 patients in the first and second waves: a multisite registry by Indian Council of Medical Research, 23 and a couple of hospital based registries. 24,25 These studies reported different patient outcomes in the first and second waves of Covid-19. Therefore, to evaluate differences in clinical and laboratory features, management patterns and outcomes among hospitalized patients at a dedicated tertiary level Covid-19 management centre in India during the first (June-December 2020) and second (January-June 2021) waves of the infection we performed an observational study.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent publication also reported a 27% mortality rate in KTRs with COVID-19, which increases to 44% in hospitalized patients and 100% in patients requiring ventilation [ 34 ]. Following the resurgence of COVID-19 in various countries, investigators have compared the epidemiology and disease outcomes between the first, second, and in some cases, third COVID-19 waves [ 21 , 25 , 33 , 35 54 ]. However, data on the effects of the second wave of COVID-19 on KTR patients and its comparison with the first wave scenario is limited and reveals diverging results [ 21 , 25 , 45 , 47 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the resurgence of COVID-19 in various countries, investigators have compared the epidemiology and disease outcomes between the first, second, and in some cases, third COVID-19 waves [ 21 , 25 , 33 , 35 54 ]. However, data on the effects of the second wave of COVID-19 on KTR patients and its comparison with the first wave scenario is limited and reveals diverging results [ 21 , 25 , 45 , 47 , 53 ]. Currently, only one single-center study has been reported from India that has retrospectively investigated the impact of the first and second waves of COVID-19 on KTR; however, the study duration of the second wave was limited to 31 st May 2021 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) infection affected >30 million people and resulted in around 390,000 deaths by June 21, across India, during the current COVID-19 pandemic. Cumulative incidence of COVID-19 was reported to be lower in children than in adults, and a greater number of pediatric kidney transplant recipients (KTRs) were infected during the second wave (5.9%) than during the first wave (0%) of COVID-19 in India [ 1 , 2 ]. In a large series of 72,314 cases in China, fewer cases of COVID-19 in children were reported than adults and only 1% of these patients were below the age of 9 years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%